The Potentials of Improving Mineral Source Additional Values in Lampung Province – A Preliminary Study - Isnugroho, K; Birawidha, D C; Amin, M (Journal of Engineering and Scientific Research, 2019)
An initial research on non-metal mineral potential was conducted for stones inLampung Province. Surveys were conducted to some districts/towns in Lampung to takesample materials. Non-metal mineral chemical composition content analysis of stoneswas conducted with X-RF method. Lampung had mineral potentials of feldspar, zeolite,kaolin, and basalt of 400,500,000 m3; 18,945,000 m3; 9,750,000 m3; 419,071,833 m3respectively. These mineral source potentials were distributed in eight districts inLampung. Processing was required to improve additional values for these mineralsources, including crushing, grinding, classifying, and concentration process.Concentration improvements were required for feldspar and kaolin minerals. Wet highintensity magnetic separator process followed by froth flotation process becamesolutions to reduce high oxide iron content. Feldspar and kaolin could be used for suchindustries of ceramic, glass, paper, and refractory. Meanwhile, the zeolite mineral fromLampung could be used for agriculture, plantation, and fishery. Basalt stone wouldhave additional values when this was processed into cast basalt, fiber, and ceramiccomposite.Keywords: feldspar, kaolin, basalt, zeolite, Lampung